Design of reactive algorithms by solving equations over automata - Chebotarev, A. N. (Cybernetics and systems analysis, 2012)
The problem of solving inequalities over finite state machines (FSMs) is considered. This problem arises in the compositional approach to the design of reactive systems. The problem is formulated and solved at the level of FSM specifications in the logical language L. It is shown how to compute the maximal solution to an inequality with respect to the operation of synchronous composition of FSMs.